KEPUASAN KERJA PADA BADAN KEPEGAWAIAN DAN DIKLAT DAERAH KABUPATEN MAJENE - Edy Edy; Muhammad Arfandi Adnan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2018)
This study aims to determine how the level of job satisfaction of the Regional Personnel and Training Agency of Majene Regency and the factors that have a relationship with the job satisfaction of the staff of the Regional Personnel and Training Agency of Majene Regency. Qualitative research focuses on how the level of job satisfaction of the Regional Personnel and Training Agency staff of Majene Regency. Data was collected by observation, questionnaire, and documentation techniques. Processed and analyzed quantitatively by presenting frequency tables and percentages to find out the percentage of respondents' answers partially to the indicators studied. The results showed that of the four factors that influence the level of job satisfaction of the Regional Personnel and Education and Training Agency staff of Majene Regency, the suitability factor of expertise with assignments turned out to not show employee job satisfaction, identity factor assignment meaning, task autonomy factor and feedback factor turned out support the work satisfaction of the apparatus.